Split-ticket voting in mixed-member electoral systems : a theoretical and methodological investigation - Plescia, Carolina (Trinity College (Dublin, Ireland). Department of Political Science, 2013)
Mixed-member electoral systems give people the opportunity of voting for the same representative body by casting two votes: one for a national party under proportional rules and one for a local candidate under majoritarian rules. Today, at least 20% of voters vote under mixed-member electoral systems. In those countries where scholarly investigations exist, hndings show that many voters split their ticket voting for a party and a candidate that are not linked. Moreover the levels of split-ticket voting have often been found to have an impact on the electoral outcome. Despite several explanations exist today, although still much debated, our knowledge of how people vote under mixed systems is still limited. This is due to methodological as well as substantive issues. This thesis examines why and how voters split their two votes. It consists of a purely methodological analysis based on the New Zealand and Scottish parliamentary elections, a comparative study across 10 mixed-member electoral systems, and also looks in depth at case studies of Japan and Italy.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin.